Experimental Ethnography : The Work of Film in the Age of Video - Russell, Catherine, 1959- (Book collections on Project MUSE., 1999)
Experimental film and ethnographic film have long been considered separate, autonomous practices on the margins of mainstream cinema. By exploring the interplay between the two forms, Catherine Russell throws new light on both the avant-garde and visual anthropology.Russell provides detailed analyses of more than thirty-five films and videos from the 1890s to the 1990s and discusses a wide range of film and videomakers, including Georges Méliès, Maya Deren, Peter Kubelka, Ray Birdwhistell, Jean Rouch, Su Friedrich, Bill Viola, Kidlat Tahimik, Margaret Mead, Tracey Moffatt, and Chantal Akerman. Arguing that video enables us to see film differently--not as a vanishing culture but as bodies inscripted in technology, Russell maps the slow fade from modernism to postmodern practices. Combining cultural critique with aesthetic analysis, she explores the dynamics of historical interruption, recovery, and reevaluation. As disciplinary boundaries dissolve, Russell contends, ethnography is a means of renewing the avant-gardism of "experimental" film, of mobilizing its play with language and form for historical ends. "Ethnography" likewise becomes an expansive term in which culture is represented from many different and fragmented perspectives.Original in both its choice of subject and its theoretical and methodologicalapproaches, Experimental Ethnography will appeal to visual anthropologists, as well as film scholars interested in experimental and documentary practices.